2001
DOI: 10.1073/pnas.101532998
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the stem cell leukemia ( SCL ) gene: A tale of two fishes

Abstract: The stem cell leukemia (SCL) gene encodes a tissue-specific basic helix-loop-helix (bHLH) protein with a pivotal role in hemopoiesis and vasculogenesis. Several enhancers have been identified within the murine SCL locus that direct reporter gene expression to subdomains of the normal SCL expression pattern, and long-range sequence comparisons of the human and murine SCL loci have identified additional candidate enhancers. To facilitate the characterization of regulatory elements, we have sequenced and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 64 publications
3
35
0
Order By: Relevance
“…Comparative genomic sequence analysis offers a powerful strategy for the identification of functionally relevant gene regulatory elements that may be later subjected to experimental evaluation. Conservation of regulatory sequences in noncoding regions between pufferfish and mammalian orthologs has been found in a number of genes, with some elements also displaying equivalent function Popperl et al 1995;Barton et al 2001). On the other hand, such comparative analyses between human and mouse genomic portions frequently result in the detection of many regions of similarity (Hardison et al 1997;Dubchak et al 2000;Gottgens et al 2000;Loots et al 2000) for which functional relevance is difficult to establish.…”
Section: Comparative Analysis Of Dystrophin Vertebrate Locimentioning
confidence: 99%
“…Comparative genomic sequence analysis offers a powerful strategy for the identification of functionally relevant gene regulatory elements that may be later subjected to experimental evaluation. Conservation of regulatory sequences in noncoding regions between pufferfish and mammalian orthologs has been found in a number of genes, with some elements also displaying equivalent function Popperl et al 1995;Barton et al 2001). On the other hand, such comparative analyses between human and mouse genomic portions frequently result in the detection of many regions of similarity (Hardison et al 1997;Dubchak et al 2000;Gottgens et al 2000;Loots et al 2000) for which functional relevance is difficult to establish.…”
Section: Comparative Analysis Of Dystrophin Vertebrate Locimentioning
confidence: 99%
“…A comprehensive analysis of the transcriptional regulation of Scl has identified several tissuespecific enhancers that are required for its appropriate expression (Barton et al, 2001;Gottgens et al, 2002;Sinclair et al, 1999). Interestingly, the enhancer specific for hematopoietic progenitors has GATA sites that are crucial for Scl enhancer activity in vivo.…”
Section: An E Box-binding Factor Is Required For Gata2 Endothelial Enmentioning
confidence: 99%
“…CNEs, and other similar highly conserved noncoding sequences, are found to cluster in the vicinity of genes implicated in transcriptional regulation and early development (Bejerano et al 2004a;Sandelin et al 2004;Woolfe et al 2005) and the majority of those tested in vivo (5/7 in mice, Nobrega et al 2003; 23/25 in fish, Woolfe et al 2005) drive expression of reporter genes in a temporal and spatial specific manner during early development. Many other studies around specific developmental genes have also identified highly conserved noncoding sequences between humans and fish that have enhancer activity (Zerucha et al 2000;Barton et al 2001;Lien et al 2002;Blader et al 2003; Lettice et al 2003;Dickmeis et al 2004;Kimura-Yoshida et al 2004;de la Calle-Mustienes et al 2005;Goode et al 2005). The association of these highly conserved sequences to genes implicated in the regulation in early development is most likely a result of the fundamental nature of the developmental process in vertebrates.…”
mentioning
confidence: 99%